The benefits of association of early diagnosis with bioactive materials for management of dental caries - dos Santos, Angélica Feltrin; Castelluccio, Tainara Tonon; Foratori-Junior, Gerson Aparecido; Rios, Daniela; Wang, Linda; Bombonatti, Juliana Fraga Soares (ARCHIVES OF HEALTH INVESTIGATION, 2021)
The concept of minimally invasive dentistry certainly promoted significant changes towards more conservative dental caries management, which allows for quality information regarding the diagnosis, prognosis, and clinical management of dental caries even regarding the maintenance of restorative procedures. This case report aimed to highlight the relevance and feasibility of a streamlined caries disease management based on caries-risk determination and minimal invasive concepts associated with bioactive materials. A 13-year-old female patient sought dental care. Clinically, active white spot lesion on the occlusal surface of right upper first premolar coming from the fissures was noteworthy under moist condition. Bitewing radiography confirmed an interproximal carious lesion involving dentin. The cavity preparation was performed as more conservative as possible, removing the carious tissue selectively and treated with bioactive materials. After 12-month follow-up, successful performance of the restoration was seen while the patient caries-risk condition seems to be under control. This clinical case demonstrates that a correct diagnosis associated with smart materials and appropriate restorative procedures can offer effective and conservative results. Evidence-based treatment benefits patient avoiding unnecessary dental compromising and the maintenance of oral health.